Organised Crime and the ecosystems of sexual exploitation in the United Kingdom: How supply and demand generate sexual exploitation and protection from prosecution - Hopkins, Matt (Trends in organized crime, 2024)
AbstractThinking about organised crime as an ecosystem is not only novel but also offers much potential to add to the theoretical and policy-based literature in this area. While organised crime is often analysed as relationships between criminal groups and consumers of illicit goods/services, little work has analysed specific forms of organised crime activities as ecosystems where different constituent parts are dependent upon each other for the crime activity to occur. This paper analyses the organisation of sexual exploitation by entrepreneurial organised crime groups selling sex in the United Kingdom. Based upon 30 interviews with 23 law enforcement forces in England and Wales and five interviews with Adult Service Website Operators; it identifies how an ecosystem is built that ensures (a) profit generation and (b) avoidance of legal prosecution. Our analysis not only illustrates how a market ‘supply’ and ‘demand’ ecosystem is generated through mutually convenient ‘organiser’, ‘marketer’ and ‘buyer’ relationships, but also how the roles of these actors ensure sexual exploitation continues.